2017
DOI: 10.1021/acs.jpcc.7b01540
|View full text |Cite
|
Sign up to set email alerts
|

Kirkendall Growth of Hollow Mn3O4 Nanoparticles upon Galvanic Reaction of MnO with Cu2+ and Evaluation as Anode for Lithium-Ion Batteries

Abstract: We report the formation of high surface area hollow Mn 3 O 4 nanoparticles that form as a result of the galvanic reaction of Cu 2+ with MnO nanocrystals concomitant with a nanoscale Kirkendall effect. The MnO nanocrystals were prepared according to the ultralarge scale synthesis reported by Hyeon, which allowed the preparation of hollow Mn 3 O 4 in multigram quantities. Ex-situ analyses with transmission electron microscopy and powder X-ray diffraction show the morphology and phase stability of the hollow part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 71 publications
1
24
0
Order By: Relevance
“…There are two slopes in the first charging curve. The first slope between 1.2 and 1.8 V mainly results from the oxidation of Mn to MnO, and the second slope, ranging from 1.9 to 2.2 V, is due to the oxidation of MnO to Mn 3 O 4 . In subsequent cycles, the discharge plateau changed to 0.4 V, which indicated structural rearrangement.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…There are two slopes in the first charging curve. The first slope between 1.2 and 1.8 V mainly results from the oxidation of Mn to MnO, and the second slope, ranging from 1.9 to 2.2 V, is due to the oxidation of MnO to Mn 3 O 4 . In subsequent cycles, the discharge plateau changed to 0.4 V, which indicated structural rearrangement.…”
Section: Resultsmentioning
confidence: 84%
“…The first slope between 1.2 and 1.8 Vm ainly results from the oxidation of Mn to MnO, and the second slope, ranging from 1.9t o 2.2 V, is due to the oxidation of MnO to Mn 3 O 4 . [49] In subsequentc ycles, the discharge plateau changed to 0.4V ,w hich indicated structural rearrangement. From the 2nd to 100th cycle, the voltage profiles were almostu nchanged, which illustrated superior cycling stability.T he above results are in good agreement with the CV curves.…”
Section: Resultsmentioning
confidence: 99%
“…[71,72] The formation of hollow structures via the Kirkendall effect has attracted substantial attention. [73][74][75] Many different hollow nano-forms including rattles, boxes, bowls, spheres, and particles of various shapes have been reported using GRR; Figure 3C The GRR has been also employed in the preparation of exfoliated 2D layered metal oxide nanosheets. The authors reported the galvanic replacement reaction of exfoliated MnO 2 nanosheets by Fe 2+ or Sn 2+ ions resulting in highly anisotropic Fe or Sn oxide nanosheets.…”
Section: Synthesis Of Nanostructured Metal Oxides By Galvanic Exchangementioning
confidence: 99%
“…Lithium-ion battery (LIB) featuring high capacity, light weight and long life, is an significant energy storage device [1][2][3][4]. Many materials (such as Li metal [5,6], Si [7], SnSe x [8], Mn3O4 [9], ReS2 [10]) can be used as the negative electrodes of LIBs. Li metal anode has been extensively studied owing to the high theoretical capacity, low density, and low redox potential [11].…”
Section: Introductionmentioning
confidence: 99%